Reasons behind cancellation of SME/LEASE finance: a case study on Uttara Finance and investment Ltd. - Hasan, Md. Mahadi (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.